Meromorphic functions of finite λ-type in a half-strip - Sokul’s’ka, N.B. (Carpathian Mathematical Publications, 2012)
The Nevanlinna characteristic of meromorphic functions in a half-strip, such that f(σ)=f(σ+ 2 π i), is introduced, and its main properties are investigated. A criterion of λ-type finiteness of holomophic in the half-strip functions in terms of Fourier coefficient of |f| is obtained.